Self-aggregates of 3,6-O,O’-dimyristoylchitosan derivative are effective in enhancing the solubility and intestinal permeability of camptothecin - Silva, Daniella S. (2017)
The aim of this work was to investigate the potential of a new 3,6-O,O’-dimyristoyl derivative amphiphilic chitosan (DMCh), in improving the solubility of camptothecin (CPT), a hydrophobic anticancer drug, and its potential oral delivery. FTIR, 1H NMR and solid-state 13C NMR spectroscopy were used to characterize DMCh and to determine its average degree of substitution (DS¯ = 6.8%). DMCh/CPT micelles size ranged from (281–357 nm), zeta potential (+32–50 mV) of encapsulation efficiency of 42–100%. The in vitro cell viability showed that DMCh/CPT micelles were able to reduce the toxicity of CPT. The in vitro permeability of CPT through Caco-2 and Caco-2/HT29-MTX intestinal models was increased up to ten fold when formulated into DMCh micelles, underlining the mucoadhesive properties of the nanocarrier. DMCh/CPT micelles are able to enhance CPT solubility and bioavailability while reduce its cytotoxicity, showing the great potential for intestinal delivery of hydrophobic drugs.